(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
In the article possible approaches to the classification of quasicomposites are analyzed, the main criteria of classification of such units with the principles of compound words differentiating are compared. The investigator proves that quasicomposites may be classified according to the same signs as proper compound words, but there are some differences which are also under consideration in this work.